Stopping at the sight of food – How gender and obesity impact on response inhibition. (1st December 2016) - Mühlberg, Christoph; Mathar, David; Villringer, Arno; Horstmann, Annette; Neumann, Jane
Abstract: Recent research indicates that reduced inhibitory control is associated with higher body mass index (BMI), higher food craving and increased food intake. However, experimental evidence for the relationship between response inhibition and weight status is inconsistent and to date has been investigated predominantly in women. In the current study, 56 participants (26 obese, 30 lean; 27 female, 29 male) performed a Food Picture Rating Task followed by a Stop Signal Task where pictures of palatable high or low caloric food or non-food items were presented prior to the Go signal. We further assessed participants' self-reported eating behavior and trait impulsivity as potential factors influencing response inhibition, in particular within the food context. Independent of BMI, women showed significantly higher liking for low caloric food items than men. This was accompanied by shorter Stop Signal Reaction Times (SSRT) after high compared to low caloric food pictures for women, and shorter SSRT in women compared to men for high caloric food. No influence of gender on SSRT was observable outside of the food context. While SSRTs did not differ between obese and lean participants across the three picture categories, we found a moderating effect of trait impulsivity on the relationship between BMI and SSRT, specifically in the high caloric food context. Higher BMI was predictive of longer SSRT only for participants with low to normal trait impulsivity, pointing at a complex interplay between response inhibition, general impulsivity and weight status. Our results support the notion that individuals with obesity do not suffer from diminished response inhibition capacity per se . Rather, the ability to withhold a response depends on context and social norms, and strongly interacts with factors like gender and trait impulsivity.